DAYA DUKUNG POLITIK DALAM PEMILIHAN UMUM KEPALA DAERAH (STUDI HISTORIS KONFLIK PEMILUKADA TOLITOLI TAHUN 2010) - Muhammad Iqbal (Journal Publicuho, 2023)
Overlapping KPU decisions regarding the status of Aziz Bestari's participation in the 2010 local leaders election of Tolitoli after his deputy Amirudin passed away at the campaign stage sparked anger and vertically violent conflict. The research aims to determine the political carrying capacity in the 2010 Tolitoli post-conflict local election. The research method used is qualitative with a historical research type, where the data source comes from previous research studies, interview documents, stories of original actors and eyewitnesses to the 2010 post-conflict local election conflict, authentic evidence in the form of KPUD's archives, photos, newspapers, online media, literature, and applicable laws/regulations. The informants were 11 people determined by purposive sampling. Furthermore, the data were analyzed using data analysis techniques according to B. Mathew Miles and A. Michael Huberman. The results of the study, the KPU's decision in the 2010 Tolitoli Regency post-conflict local election damaged the values of harmony in society, the interpretation of Article 63 paragraph 2 of Law No.32/2004 was not easy to understand, especially by the implementor, there was a violation of the election organizers' code of ethics, and the attitude of the KPUD those who print new ballots without waiting for the decision of the Constitutional Court.